2014
DOI: 10.2139/ssrn.2438894
|View full text |Cite
|
Sign up to set email alerts
|

Youth Training Programs Beyond Employment. Experimental Evidence from Argentina

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A more complex interpretation of subgroup effects emerged for gender differences, whereby, trials identified a significant effect on employment [29], a reduction in welfare receipt [30], and no short-term (i.e. <18 months) wage suppression [31] for females only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more complex interpretation of subgroup effects emerged for gender differences, whereby, trials identified a significant effect on employment [29], a reduction in welfare receipt [30], and no short-term (i.e. <18 months) wage suppression [31] for females only.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting, however, that intervention costs per recipient are low (e.g. $750 [29]; $1722 [30]). Although it is notoriously difficult to cost up the net social benefit of an individual moving from NEET to non-NEET status, where interventions are simple (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining studies either do not find any effect -for example, the programme PROIMUJER in Uruguay (Alesina et al, 2005) -or the positive impact is confined solely to women -such as in the case of Jóvenes in Acción in Colombia (Attanasio et al, 2011). Elsewhere, other benefits associated with training programmes were identified, such as enhanced access to credit and improvements in non-cognitive skills, as in the case of Entra 21 in Argentina (Alzúa et al, 2013) and Galpão in Brazil (Calero et al, 2014), respectively -irrespective of whether these positive impacts actually improved labour market outcomes.…”
Section: Training Programmesmentioning
confidence: 99%
“…27 Randomized controlled trials (RCT) have been performed and analyzed in four programs in the region: Entra21 in Argentina, three years after training; Jóvenes en Acción in Colombia, ten years after; Juventud y Empleo in the Dominican Republic, six years after; and Projoven in Peru, three years after. In general, these programs continue to have a positive impact on the quality of employment in the medium and long term (Alzúa, Cruces, and López, 2015;Attanasio et al, 2015;Kugler et al, 2015;Ibarrarán et al, 2015;Díaz and Rosas-Shady, 2016).…”
Section: Youth Training Programs: Help Getting Startedmentioning
confidence: 99%